Faktor Risiko yang Mempengaruhi Perilaku Seksual Pranikah Remaja - Kartini Estelina Tungka; Nursalam Nursalam; Rizki Fitryasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the risk factors that influence premarital sex behavior among adolescents. The method used is a systematic review following the PRISMA guidelines by searching for articles in the Pubmed, Scopus, ScienceDirect and Proquest databases. The results showed that parental supervision had a significant indirect relationship with the premarital sexual behavior of adolescents through attitudes about premarital sex, attitudes about premarital sexuality and intention to behave sexually. Most adolescents have less sexual and reproductive health knowledge, especially early adolescents. As for attitudes towards premarital sexual behavior, the influence of friends is vital to do risky things that must be avoided. In conclusion, the risk factors influencing premarital sexual behavior among adolescents include lack of knowledge, adolescent perceptions of premarital sex, parental supervision, strong peer influence, weak information about health services and sex education for adolescents. Keywords: Risk Factors, Indonesia, Premarital Sex Adolescents